Over‐The‐Top Technique for ACL Reconstruction: Advantages, Disadvantages, and Postoperative Complications - Haocheng Du; Lin Li; Ziwen Qin; Jiang Guo; Xintao Zhang (Orthopaedic Surgery)
ABSTRACT Anterior cruciate ligament (ACL) injuries are the most common knee joint injuries related to sports activities in clinical practice. For treating ACL injuries, anatomical reconstruction surgery is often the preferred method. The over‐the‐top (OTT) technique is a surgical approach that eliminates the need for creating a femoral tunnel. According to the existing literature, the OTT technique offers distinct advantages, particularly for skeletally immature individuals and in revision cases. Currently, femoral tunnel failure is the most common cause of ACL reconstruction failure, which can lead to less than optimal postoperative performance of the ACL and a higher likelihood of needing a revision. Additionally, mistakes in the placement of the femoral tunnel and the subsequent risk of tunnel enlargement can increase the complexity of revision procedures, ultimately reducing the long‐term clinical effectiveness for patients. In contrast, the OTT technique has shown excellent biomechanical performance, avoids the need for bone tunnels, is economically practical, and has been proven to provide satisfactory therapeutic outcomes both in the short and long term, especially for skeletally immature individuals and in revision cases. The OTT technique is deemed a safe and effective surgical method for treating ACL injuries. In summary, the OTT technique has unique benefits for skeletally immature individuals and in revision cases, making it a viable option worth considering. Level of evidence V.